CONTRIBUIÇÃO DOS ATRIBUTOS QUÍMICOS DO SOLO NO DESENVOLVIMENTO VEGETATIVO DO PARICÁ EM DIFERENTES SISTEMAS DE CULTIVO - Rodrigues, Possidônio Guimarães; Ruivo, Maria De Lourdes Pinheiro; Piccinin, Jorge Luiz; Jardim, Mário Augusto Gonçalves (Universidade Federal de Santa Maria, 2016)
This study aimed to evaluate some chemical components of an Oxisol and the relationship with the vegetative development of paricá [Schizolobium amazonicum (Huber ex Ducke)] in different cropping systems in reforestation areas in the municipality of Tailandia, northeast paraense. Evaluated the PP [paricá x pueraria (Pueraria phaseoloides)], PA [paricá x acacia (Acacia mangium)] and P (monoculture paricá) systems conducted in 5 years by the company G.M. Sufredini Industrial LTDA and collected soil samples at a depth of 0-20 cm for analysis of pH, total C and N, H + Al, available P, exchangeable Ca, Mg, K and Al and calculated values ​​of C/N, SB, T, V and m. The vegetative development of paricá was assessed by survival, mortality and the number of defective plants beyond the DBH. The results showed that the increase in nitrogen content of the soil in PP treatment, the low soil fertility in PA treatment, but where paricá achieved the highest average in diameter (DBH = 16.64 cm) and greater survival rate in P treatment (90.63%). It was concluded that the soil-plant relationship in paricá and pueraria systems and monoculture paricá contributed to the establishment of individuals paricá.

Objetivou-se avaliar alguns componentes químicos de um Latossolo e a relação com o desenvolvimento vegetativo do paricá [Schizolobium amazonicum (Huber ex Ducke)] em diferentes sistemas de cultivo em áreas de reflorestamento no município de Tailândia, nordeste paraense. Foram avaliados os sistemas PP [paricá x puerária (Pueraria phaseoloides)], PA [paricá x acácia (Acacia mangium)] e P (paricá monocultivo) conduzidos em 5 anos pela empresa G.M. Sufredini Industrial Ltda. e coletadas amostras de solos na profundidade de 0-20 cm para análise de pH, C e N totais, H+Al, P disponível, Ca, Mg, K e Al trocáveis e calculados os valores de C/N, SB, T, V e m. O desenvolvimento vegetativo do paricá foi avaliado pela sobrevivência, mortalidade e no número de plantas defeituosas além do DAP. Os resultados mostraram que houve o aumento no teor de nitrogênio do solo no tratamento PP; a baixa fertilidade do solo no tratamento PA, mas onde o paricá obteve a maior média em diâmetro (DAP = 16,64 cm) e a maior taxa de sobrevivência no tratamento P (90,63%). Conclui-se que a relação solo-planta nos sistemas paricá e puerária e paricá em monocultivo contribuiu para o estabelecimento dos indivíduos de paricá.
THE CONTRIBUTION OF SOIL CHEMICAL ATTRIBUTES GROWTH VEGETATIVE DEVELOPMENT OF PARICÁ IN DIFFERENT CULTIVED SYSTEMS
Keywords: silviculture; DBH; soil fertility; silvicultura; DAP; fertilidade do solo